Multi‐Ethnic Minority Nurses' Knowledge and Practice of Genetics and Genomics. Issue 4 (23rd April 2014) - Coleman, Bernice; Calzone, Kathleen A.; Jenkins, Jean; Paniagua, Carmen; Rivera, Reynaldo; Hong, Oi Saeng; Spruill, Ida; Bonham, Vence
Abstract Purpose Exploratory studies establishing how well nurses have integrated genomics into practice have demonstrated there remains opportunity for education. However, little is known about educational gaps in multi‐ethnic minority nurse populations. The purpose of this study was to determine minority nurses' beliefs, practices, and competency in integrating genetics‐genomics information into practice using an online survey tool. Design A cross‐sectional survey with registered nurses (RNs) from the participating National Coalition of Ethnic Minority Organizations (NCEMNA). Two phases were used: Phase one had a sample of 27 nurses who determined the feasibility of an online approach to survey completion and need for tool revision. Phase two was a main survey with 389 participants who completed the revised survey. The survey ascertained the genomic knowledge, beliefs, and practice of a sample of multi‐ethnic minority nurses who were members of associations comprising the NCEMNA. Methods The survey was administered online. Descriptive survey responses were analyzed using frequencies and percentages. Categorical responses in which comparisons were analyzed used chi square tests. Findings About 40% of the respondents held a master's degree (39%) and 42% worked in direct patient care. The majority of respondents (79%) reported that education in genomics was important. Ninety‐five percent agreed or strongly agreed that family health history could identify at‐risk families, 85% reported knowing how to complete a second‐ and third‐generation family history, and 63% felt family history was important to nursing. Conversely, 50% of the respondents felt that their understanding of the genetics of common disease was fair or poor, supported by 54% incorrectly reporting they thought heart disease and diabetes are caused by a single gene variant. Only 30% reported taking a genetics course since licensure, and 94% reported interest in learning more about genomics. Eighty‐four percent believed that their ethnic minority nurses' organizations should have a visible role in genetics and genomics in their communities. Conclusions Most respondents felt genomics is important to integrate into practice but demonstrated knowledge deficits. There was strong interest in the need for continuing education and the role of the ethnic minority organizations in facilitating the continuing education efforts. This study provides evidence of the need for targeted genomic education to prepare ethnic minority nurses to better translate genetics and genomics into practice. Clinical Relevance Genomics is critical to the practice of all nurses, most especially family health history assessment and the genomics of common complex diseases. There is a great opportunity and interest to address the genetic‐genomic knowledge deficits in the nursing workforce as a strategy to impact patient outcomes.